Chernets M.V., Chernets Ju.M. The estimation of contact strength, wear and durability of cylindrical spur tractive gear of electric locomotive at high-altitude correction of engagement. - Чернець, М. В.; Чернець, Ю. М. (Problems of Tribology, 2018)
For cylindrical spur tractive gear it has been conducted the calculation of maximal contact pressures, teeth wear and durability at high-altitude correction of engagement. It has been established the regularities of tribocontact pressures change in engagement after reaching the permissible wear depending on shift coefficients in the phases of double – single – double engagement. It is observed the considerably larger value of maximal contact pressures at the entrance into single-tooth engagement than at the entrance into double-tooth engagement. Depending on shift coefficients, maximal (permissible) wear of wheel teeth would arise in different specific contact points: at the entrance into single-tooth engagement in non-corrected gear and at the exit out of it in the presence of correction. Gear durability has its optimum at shift coefficients = 0 and in this case it is 1,245 larger than in non-corrected gear.